2000
DOI: 10.1111/j.0014-3820.2000.tb00011.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in Stressful Environments. I. Phenotypic Variability, Phenotypic Selection, and Response to Selection in Five Distinct Environmental Stresses

Abstract: Abstract. Considerable debate has accompanied efforts to integrate the selective impacts of environmental stresses into models of life-history evolution. This study was designed to determine if different environmental stresses have consistent phenotypic effects on life-history characters and whether selection under different stresses leads to consistent evolutionary responses. We created lineages of a wild mustard (Sinapis arvensis) that were selected for three generations under five stress regimes (high boron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
159
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 200 publications
(170 citation statements)
references
References 137 publications
(152 reference statements)
10
159
1
Order By: Relevance
“…Vice versa, it could also be a passive stress response with no adaptive value. For example, delayed flowering was also observed in other drought experiments (Fox 1990b;Blum 1996;Stanton et al 2000;Peñuelas et al 2004) and has been attributed to a severe growth limitation. Our own observations in the field indeed indicated that most species developed faster in the wetter treatments (ESM, Supplementary Table 1) as suggested by Sachs (1999).…”
Section: Flowering Timementioning
confidence: 52%
See 1 more Smart Citation
“…Vice versa, it could also be a passive stress response with no adaptive value. For example, delayed flowering was also observed in other drought experiments (Fox 1990b;Blum 1996;Stanton et al 2000;Peñuelas et al 2004) and has been attributed to a severe growth limitation. Our own observations in the field indeed indicated that most species developed faster in the wetter treatments (ESM, Supplementary Table 1) as suggested by Sachs (1999).…”
Section: Flowering Timementioning
confidence: 52%
“…However, the treatment effects were surprisingly inconsistent. In three species in the Mediterranean site, we indeed found an earlier onset of reproduction in the drought treatment, which could be indicative of a drought-escape strategy (Geber and Dawson 1990;Stanton et al 2000;McKay et al 2003;Sherrard and Maherali 2006;Franks 2011). However, this pattern did not occur in the other species and it was even reverted in one of them (B. didyma).…”
Section: Flowering Timementioning
confidence: 57%
“…Many studies suggest that trade-oVs may exist between traits involved in dehydration-avoidance and dehydrationescape strategies (Geber and Dawson 1990;Stanton et al 2000;McKay et al 2003; but see Sherrard and Maherali 2006). In particular, higher WUE is expected to be favored in water-limited environments, where minimizing water loss allows the plant to extend its growth over a longer period.…”
Section: Dehydration Avoidance Versus Escapementioning
confidence: 99%
“…It is well established that the interaction of many environmental and genetic factors can contribute to Xowering time variation in plants (reviewed in Simpson and Dean 2002;Koornneef et al 2004), and that the optimal timing of Xowering may vary tremendously across diVerent habitats in response to external cues, including day length (Weinig et al 2002), light levels (Stanton et al 2000), temperature (Eckhart et al 2004), nutrient level (Stanton et al 2000), and water availability (Fox 1990;Eckhart et al 2004;Franke et al 2006). While we are still in the early stages of identifying the speciWc environmental cues that inXuence Xowering time patterns in Mimulus, recent studies suggest that local adaptive Xowering-time diVerences are a response to the diVering intensity of seasonal drought in coast and inland habitats of M. guttatus (Hall and Willis 2006;Lowry et al 2008).…”
Section: Key Traits For Response To Water Limitation In Mimulusmentioning
confidence: 99%
See 1 more Smart Citation